2021
DOI: 10.3389/fpsyg.2021.719827
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Career Motivations, Strengths, and Challenges of Autistic and Non-autistic University Students: Insights From a Participatory Study

Abstract: Supports for the growing number of autistic university students often focus on helping them succeed in university. However, even educated autistic people experience discrimination and other challenges which can make it very difficult for them to obtain meaningful jobs. Little remains known about how universities can better support their autistic students and alumni in overcoming barriers to meaningful employment. In this participatory study, a team of autistic and non-autistic researchers asked autistic (n = 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 61 publications
2
16
0
Order By: Relevance
“…This trend resonates with the study by Wood and Happé (2021) where of n = 149 autistic teachers or education staff surveyed, 80% identified as female. It also echoes the study by Cheriyan et al (2021) who report that autistic students were more motivated to seek a role in higher education than non-autistic students. They also found that female autistic students tended to opt for jobs, which helped others compared to their male autistic peers.…”
Section: Discussionsupporting
confidence: 76%
“…This trend resonates with the study by Wood and Happé (2021) where of n = 149 autistic teachers or education staff surveyed, 80% identified as female. It also echoes the study by Cheriyan et al (2021) who report that autistic students were more motivated to seek a role in higher education than non-autistic students. They also found that female autistic students tended to opt for jobs, which helped others compared to their male autistic peers.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, self-compassion requires a desire to grow, to look forward with hope for success and to build on positive attributes of the self. Neurodivergent students’ self-belief and ambitions for employment post-graduation are often challenged by negative experiences of academic discrimination ( Cheriyan et al, 2021 ). Within schools and universities, where being neurodivergent often makes you a more ‘troublesome’ student, thriving is typically curtailed, with negative implications for future hopefulness.…”
Section: Learning From Applications Of Compassion In Other Fieldsmentioning
confidence: 99%
“…Before concluding, it is worth considering one of the many impactful outputs of accessible and compassionate pedagogic practice; that is, a carry-forward of positive academic experiences in terms of student self-esteem, hopefulness and preparedness for the workplace ( Kuriyan et al, 2013 ; Cheriyan et al, 2021 ). These conditions occur when students find their place and their strengths in educational settings.…”
Section: Employability and Post-universitymentioning
confidence: 99%
“…However, such an industry-specific focus belies the actual and varied interests and aspirations of prospective autistic employees. For example, in a participative study, university students on the autism spectrum most frequently listed a helping profession as their career goal (39%), whereas only 11% indicated an interest in a computer/math profession and 17% indicated an interest in science (Cheriyan et al, 2021). Not exploring an array of industries and jobs of interest to autistic people is likely to produce research that reinforces rather than dispels stereotypes.…”
Section: Discussionmentioning
confidence: 99%